Pets for pediatric transplant recipients: To have or not to have - Platero, Lucía; Garcia-Sanchez, Paula; Sainz, Talía; Calvo, Cristina; Iglesias, Irene; Esperon, Fernando; de la Fuente, Ricardo; Frauca, Esteban; Perez-Martinez, Antonio; Mendez-Echevarria, Ana (Frontiers in Veterinary Science, 2022)
Pets have many health, emotional and social benefits for children, but the risk of zoonotic infections cannot be underestimated, especially for immunosuppressed patients. We report the recommendations given by health professionals working on pediatric transplantation to families regarding pet ownership. An online survey addressing zoonosis knowledge and recommendations provided by health care practitioners regarding pets was distributed via international medical societies and research networks to clinicians treating pediatric transplant recipients. A total of 151 practitioners from 28 countries participated in the survey. Up to 29% of the respondents had treated at least one case of zoonosis. Overall, 58% considered the evidence too scarce and 23% recognized to be unaware or outdated. Still, 27% of the respondents would advise against buying a pet. Practitioners already owning a pet less frequently advised patients against pet ownership, whereas non-pet-owners were more keen to advise against pet ownership (p=0.058). A 61% of the participants stated that there were no institutional recommendations regarding pets in their centers/units. However, 43% of them reported therapeutic initiatives that involved animals in their centers. Infectious disease specialists were more likely to identify zoonotic agents among a list of pathogens compared to other specialists (p<0.05). We have observed a huge heterogeneity among the recommendations that health care providers offer to families in terms of risk related to pet ownership for transplant recipients. The lack of evidence regarding these recommendations results in practitioners’ recommendations based on personal experience.